Bilirubin Levels in Cases of Neonatal Jaundice Treated with Phototherapy at Kalisat Hospital - Lulut Sasmito; Ratna Suparwati; Herlidian Putri; Lia Ulfah Luthfiana (Health Notions, 2018)
Physiological jaundice is jaundice arising on the second or third day and will disappear within the first ten days. This study aimed to analyze the decrease in the level of billirubin in the case of neonatal jaundice undergoing phototherapy at Kalisat Hospital, using a retrospective design. The sample size was 35 people who were selected by simple random sampling technique. Data obtained from medical record and observation. The collected data were analyzed using T test. The result of data analysis showed that there was a decrease of bilirubin levels after the administration of phototherapy. Keywords: Bilirubin, Jaundice, Phototherapy